Upregulation of miRNA‐143, ‐145, ‐192, and ‐194 in esophageal epithelial cells upon acidic bile salt stimulation. Issue 6 (5th September 2013) - Bus, P.; Siersema, P. D.; Verbeek, R. E.; van Baal, J. W. P. M.
Summary Barrett's esophagus (BE) is a metaplastic condition of the distal esophagus that occurs because of chronic gastroesophageal reflux. Previous studies have identified BE‐specific microRNAs (miRNAs) in comparison with normal squamous epithelium (SQ). We hypothesized that BE‐specific miRNAs could be induced in esophageal SQ cells by exposure to acid and/or bile salts. We aimed to determine whether BE‐specific miRNAs are upregulated in an esophageal SQ cell line (Het‐1A) in an environment with acid and/or bile salts and whether this is nuclear factor‐κB (NF‐κB) dependent. Acid and/or bile salt incubations were performed in Het‐1A cells. Experiments were performed with or without inhibiting the NF‐κB pathway. Quantitative reverse transcriptase polymerase chain reaction was performed to determine expression of miRNA‐143, ‐145, ‐192, ‐194, cyclo‐oxygenase‐2 (COX2), mucin 2 (MUC2), and sex determining region Y‐box 9. For validation, we determined levels of these miRNAs in biopsies from patients with reflux esophagitis and normal SQ. Significantly increased expression levels of miRNA‐143 (2.7‐fold), ‐145 (2.6‐fold), ‐192 (2.0‐fold), ‐194 (2.2‐fold), COX2, MUC2, and sex determining region Y‐box 9 were found upon acidic bile salt incubation, but not upon acid or bile salt alone. NF‐κB pathway inhibition significantly decreased miRNA‐143, ‐192, ‐194, COX2, and MUC2 expression. Additionally, miRNA‐143, ‐145 and ‐194 expression was increased in reflux esophagitis biopsies compared with normal SQ, but no changes were found in miRNA‐192 expression. Our findings suggest that upregulation of BE‐specific miRNAs by acidic bile may be an early event in the transition of SQ to BE and that their expression is partly regulated by the NF‐κB pathway.